ELECTROCARDIOGRAPHY PATTERNS IN PATIENTS WITH PROXIMAL LEFT ANTERIOR DESCENDING CORONARY ARTERY STENOSIS - Shrestha, Manoj; Bhusal, Pramod (Journal of Chitwan Medical College, 2024)
Background: Stenosis of proximal left anterior descending coronary artery presents with diverse electrocardiographic patterns. This study aimed to determine different types of ECG changes and their frequency in patients with proximal left anterior descending coronary artery stenosis.Methods: This descriptive cross-sectional study was conducted at the Department of Cardiology, College of Medical Sciences, Bharatpur from Ist June 2023 to 30 October 2023. Patients who underwent coronary angiography and had proximal left coronary artery stenosis were included in the study. Total 80 such patients were evaluated. Electrocardiographic changes in these patients was noted. Proximal left anterior descending coronary artery stenosis was independent variable and ECG changes were dependent variables. The ECG changes were ST elevations in leads I, aVL and precordial leads V1-V6, ST elevations in V1-V6, De Winter’s T-wave pattern, acute LBBB and Wellen’s Syndrome. Frequency of varying electrocardiographic changes in proximal left anterior descending coronary artery stenosis was evaluated.Results: Electrocardiographic analysis of proximal left anterior descending artery revealed diverse patterns. 37.5% (n=25) had ST elevations in leads I, aVL and V1-V6. 25% (n=20) had ST elevations in V1-V6. De Winter’s T-wave pattern was seen in 16.25% (n=13) patients. Left bundle branch block was present in 15% (n=12). A Wellen’s Syndrome was present in 12.5% (n=10).Conclusions: Proximal LAD artery stenosis reveals significant diversity in ECG patterns.